2007
DOI: 10.1002/ejic.200700507
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a New Guanidine–Borane Complex and a Dinuclear Boron(II) Hydride with Bridging Guanidinate Ligands

Abstract: We report the synthesis and structural characterization of the new monomeric borane complex H3B·hppH (hppH = 1,3,4,6,7,8‐hexahydro‐2H‐pyrimido[1,2‐a]pyrimidine), which represents the first example of a structurally characterized 1:1 complex between hppH and a group 13 element hydride. Significant intramolecular and, in the crystalline phase, intermolecular H···H contacts are established in this complex. It is shown that the complex can be used as a precursor to new dinuclear boron(II) compounds featuring a B–B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
73
0
20

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 23 publications
4
73
0
20
Order By: Relevance
“…Although we have previously reported the structure of 3, [7] we have only now found a route to 3 in high yield and purity. The initial thermal dehydrogenation of 1 proved not to be the ideal route to 3; however, we recently showed that 1 can be catalytically dehydrogenated with [{Rh(1,5-cod)Cl} 2 ] in toluene at 80 8C to give 2 (with a B···B separation of 306.5 pm).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Although we have previously reported the structure of 3, [7] we have only now found a route to 3 in high yield and purity. The initial thermal dehydrogenation of 1 proved not to be the ideal route to 3; however, we recently showed that 1 can be catalytically dehydrogenated with [{Rh(1,5-cod)Cl} 2 ] in toluene at 80 8C to give 2 (with a B···B separation of 306.5 pm).…”
mentioning
confidence: 92%
“…The molecular structures of 1, 2, and 3 from X-ray diffraction results. [7,8] [a] The energy-minimum structures were calculated at the B3LYP/6-31 + + G** level. The d( …”
mentioning
confidence: 99%
“…In our studies we used the doubly base-stabilized diborane(4) [HB(m-hpp)] 2 (1), which was synthesized as described previously by catalytic dehydrogenation of the adduct H 3 B·hppH (Scheme 2). [4] We recently reported on different aspects of the reactivity of 1. For example, sulfuration was shown to give [HB(m-hpp)] 2 (m-S), [5] and protonation leads to the cation and doubly base-stabilized B 2 H 5…”
mentioning
confidence: 99%
“…Entsprechend ihren Rechnungen liegt das C 2v -symmetrische Isomer mit einem B 3 (1), das, wie bereits beschrieben, durch katalytische Dehydrierung des Addukts H 3 B·hppH (Schema 2) hergestellt wird. [4] Kürzlich berichteten wir über verschiedene Aspekte der Reaktivität von 1. Es wurde beispielsweise gezeigt, dass Sulfurierung [HB(mhpp)] 2 (m-S) ergibt, [5] während Protonierung zu dem kationischen B 2 H 5…”
unclassified